STUDY ON A BETTER MANAGEMENT IN A MODERN FARM USING DIFFERENT FUELS FOR TRACTOR ENGINES - Mariana DUMITRU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In a modern agricultural farm, efficient management of power used in the farm is fully as important as efficient management of machinery. This paper studied the importance of using one or other type of fuels in the final result, which is the efficiency of the engine used by a tractor or other machinery used in the farm. The fuels considered are diesel oil, hydrogen, liquified petroleum gas, premium gasoline, propane, methanol and ethanol. The manager decision of using one or another fuel is based on each fuel energy value, combustion characteristics and economy. The farm manager also must consider the adjustments that must be made to tractor engine if using one or another fuel.